Wild Edible Fruits of Palpa District, West Nepal - Mahato, Ras Bihari (Journal of Natural History Museum, 2015)
This paper documents the wild edible fruits of tropical and subtropical forest of Palpa District, West Nepal. Thirty-seven plant species under 17 families and 27 genera were identifi ed as wild edible fruit. Over 86% percent of them were trees and shrubs (32 species), 11% herbs (4 species) and the remaining 3% (1 species) woody climbers. Moraceae (9 species), Rosaceae (7 species), Anacardiaceae, Berberidaceae, Combretaceae, Fabaceae, Solanaceae and Rutaceae (2 species each) were the most common families constituting about 75.7% of edible plants. The remaining 24.3% (9 species) of edible plants were distributed among 9 families and 9 genera. A considerable number of wild fruits are sold in market. These are Aegle marmelos, Artocarpus integra, Artocarpus lakoocha, Choerospondias axillaris, Myrica esculenta, Phoenix humilis, Phyllanthus emblica, Prunus persica, Pyracantha crenulata, Tamarindus indica, Terminalia bellirica, Terminalia chebula, Zanthoxylum armatum and Zizyphus mauritiana. Medicinal uses of some major economically important fruits are also documented. J. Nat. Hist. Mus. Vol. 28, 2014: 127-136